Poetics of contingency. Issue 3 (16th March 2018) - White, Gillian
ABSTRACT: How can a poem be read for its contingency? Can contingency be figured in or by a poem? (Which poem? When? Read how, and by whom?). This essay describes a US 'contingency poetics' of the 1990s, and weighs its claims against a sampling of twentieth-century poems preoccupied with contingency, some written under the sign of this poetics, some not. It does so to explore the critical conundrums that attend thinking about poetry's possible relations to 'contingency' – including poetry's reputation for generic resistance to it – in part to articulate a knot of interpretive challenges central to the history of criticism of the 1990s, from the status of 'narrative' in poetry to the persistence of lyric reading in avant-garde criticism. There are challenges herein described still relevant for this historicist reader of poems, and that have bearing on how, as critics, we imagine our narrative labours on behalf of poems.